Community Perceptions on Corona Virus- A Survey of Garhshankar Block of Hoshiarpur district, Punjab - VIRDI, NEERAJ; SHIVAM; KAUR, JASPREET; KAUR, MANBEER (The journal of contemporary issues in business and government, 2021)
Nature’s forces seem to have rallied around on reclaim their upset balance. Humans have disturbed the natural forces by exploiting Earth’s resources in an irresponsible manner. The history of our planet has witnessed several pandemics that threatened to successively decimate mankind some examples are the Antonine Plague (165 AD), Leprosy (11th century), the Black Death (1350), the Goat Plague of London (1665), First Cholera Pandemic (1817), HIV/AIDS (1981), and the most recent COVID-19 or Corona (2021) that is coming in several phases. All these geographically widespread epidemics have led to millions of deaths around the globe. The Corona virus appears to have mutated in India in 2021 after the world had paid its toll in 2020. Lives everywhere have been experiencing an almost complete lockdown to contain this viral disease. The focal point of this research paper is to determine the awareness levels of the population with respect to the COVID-19 crisis. Do people believe in the existence of Corona? What precautions are they taking to protect themselves? How confident are they of the effectiveness of the vaccine? The study was carried out in the Garhshankar block of Hoshiarpur district in Punjab among 305 respondents through an online questionnaire methodology to ascertain their views on the ongoing pandemic. The findings of the study are expected to be the pre-cursor of launching programs to address the needs of the community in facing the pandemic situation successfully.